Bacteriological Study Of Chronic Suppurative Otitis Media - Adnan Hadi , Ammar; Hadi Khammas, Ammar; Mahdi Abbas Alsaeed, Wissam (Diyala Journal of Medicine, 2020)
Background: Chronic suppurative otitis media is a destructive disease of middle ear cleft that can progress rapidly. Medical treatment which depend on proper antibiotic selected from culture and sensitivity were prescribed, otherwise process goes to intra or extracranial complication. Objective: Relation of certain clinical features to each isolated bacteria. The types of bacteria in chronic suppurative otitis media. Drug sensitivity for each isolated bacteria. Patients and Methods: Forty-six patients enrolled in the current study, 41 patients have unilaterally discharged ears and 5 bilaterally discharged ears. The total ears are 51 ears were taken for examination, microorganism isolation, biochemical tests and then culture and sensitivity tests. Regarding ear examination, it involved clinical picture. Regarding laboratory tests certain types of biochemical test, 4 types of media were used for isolation of bacteria and in culture and sensitivity tests. 16 types of drugs used for culture and sensitivity test. All collected data putted in a questionnaire, tables and histograms. Results: 55% of patients with profuse discharge while 45% scanty amount of ears discharge. Mucosal type of chronic suppurative otitis media were 53% while 47% of squamous type. Regarding types of bacteria, Pseudomonas aeruginosa of 41.2%, Staphylococcus aureus of 11.6% are the most common isolated bacteria. Regarding drug sensitivity, Imipenem, Meropenem of 100% sensitivity, Amikacin of 92% sensitivity while Cefixime of 62% resistance. Conclusion:There was a relation between particular suppurative chronic otitis media causing microorganisms and specific discharge.Pseudomonas aeruginosa and Staphylococcus respectively are the most common pathogens. Imipenem and Meropenem are the most effective drugs